2020
DOI: 10.14689/ejer.2020.86.9
|View full text |Cite
|
Sign up to set email alerts
|

School Administrators’ Opinions Related to the Values that should Be Gained to Classroom Teachers through In-Service Training

Abstract: Purpose: Social changes and developments in educational policies bring along changes in the values of the teaching profession. The changing values increase the in-service training needs of the teachers. Although it is aimed to gain prospective teachers the values of the teaching profession in the pre-service period, it is seen that the target is not sufficiently achieved. The present research aims to investigate administrators' opinions regarding the values that should be gained among classroom teachers throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
1
5
0
1
Order By: Relevance
“…Similar findings are seen in previous studies, and it reinforces this interpretation. Substantially, there are similar results in the studies conducted by Aybek andKaratas (2016), Coskun (2016), Karatas (2013), Karabacak (2016), Sezer, Karabacak, Korkmaz andKucuk (2019), Kocyigit and Karadag (2017), Tunca and Saglam (2013). In these studies, the participants envisage that teachers should always consider being a positive role model for their students, respecting differences, having personal and social responsibility, being against violence, being open to cooperation, having the ethic principals including honesty, universality, professional responsibility, conscience and fairness.…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 77%
See 1 more Smart Citation
“…Similar findings are seen in previous studies, and it reinforces this interpretation. Substantially, there are similar results in the studies conducted by Aybek andKaratas (2016), Coskun (2016), Karatas (2013), Karabacak (2016), Sezer, Karabacak, Korkmaz andKucuk (2019), Kocyigit and Karadag (2017), Tunca and Saglam (2013). In these studies, the participants envisage that teachers should always consider being a positive role model for their students, respecting differences, having personal and social responsibility, being against violence, being open to cooperation, having the ethic principals including honesty, universality, professional responsibility, conscience and fairness.…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 77%
“…In these studies, the participants envisage that teachers should always consider being a positive role model for their students, respecting differences, having personal and social responsibility, being against violence, being open to cooperation, having the ethic principals including honesty, universality, professional responsibility, conscience and fairness. In addition, in a study conducted by Sezer, Karabacak, Korkmaz and Kucuk (2019), professional skills should be gained to teachers through in-service training, including communication skills, technology using skills, pedagogical content knowledge, planning skills, material designing and using skills.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…Alanyazında değer kavramı ve değerler eğitimi incelendiğinde; sınıf öğretmenlerinin değer eğitimine, değer eğitiminde etkili olan faktörlere ve değer eğitimi uygulamalarına ilişkin görüşleri (Aksoy, 2017;Ateş, 2014;Aydın, 2019;Çelik, 2020;Eryılmaz, 2016;Gözel, 2018;Gürhan, 2017;Kara, 2017;Taymur, 2015), öğretmenlerin değerler eğitiminde kullanılan araçgereç ve materyallere ilişkin görüşleri (Abukan, 2019;Uzuner, 2019), sosyal bilgiler dersinde ve müfredatında yer alan değerler eğitimi ve değerler eğitimi uygulamalarına ilişkin öğretmen görüşleri (Baysal, 2013;Can, 2008;Öğretici, 2011;Yalçın, 2019), okul öncesi öğretmenlerinin değerler eğitimine, değerler eğitimi programına ve değerler eğitimi uygulamalarına ilişkin görüşleri, (Çetin Korkmaz, 2019;Eren, 2018;Erkuş, 2012;Kuzu, 2015;, farklı branşlardaki öğretmenlerin değerler eğitimi, değerler eğitimi programı ve değerler eğitimi uygulamalarına ilişkin görüşleri (Baydır, 2018;Çelik, 2020;Özdemir, Boydak Özan ve Akgün, 2017;Özdaş, 2013;Şentürk, 2020), sınıf öğretmenlerinin hizmet içi eğitimle kazanması gereken değerlerin yönetici görüşleri açısından değerlendirilmesi (Sezer, Karabacak, Küçük ve Korkmaz, 2020) değerler eğitimine ilişkin öğretmen adaylarının görüşleri (Acar Başeğmez ve Er, 2017;Kurtdede Fidan, 2009;Şahin, 2019), üstün yetenekli öğrencilerde değerler eğitimine ilişkin idareci ve öğretmen görüşleri (Turgut Yıldırım, 2019) incelenmiştir. Bu çalışmanın amacı ilkokul öğretmenlerinin değer eğitimi uygulamalarına ilişkin görüşlerini belirlemektir.…”
Section: öğRetmenlerin Değerler Eğitimi Uygulamalarına Yönelik Görüşleriunclassified
“… Sezer et al (2020) in their research conducted with school principals, found that unconditional acceptance, as a professional value, should be gained and developed through in-service training, to help teachers to understand the positive and negative consequences of this concept, both on themselves and on their students. Despite the high relevance for unconditional acceptance in educational settings there is a lack of studies on interventions aimed to increase the unconditional acceptance applied to teachers.…”
Section: Introductionmentioning
confidence: 99%